1996
DOI: 10.1021/ja962470s
|View full text |Cite
|
Sign up to set email alerts
|

Linear Oligo(ferrocenyldimethylsilanes) with between Two and Nine Ferrocene Units:  Electrochemical and Structural Models for Poly(ferrocenylsilane) High Polymers

Abstract: In order to gain insight into the electrochemical and conformational properties of the prototypical high polymeric poly(ferrocenylsilane), poly(ferrocenyldimethylsilane) [Fe(η-C5H4)2SiMe2] n 6, three series of oligo(ferrocenylsilanes) R-fc-[SiMe2-fc] n - 1-R‘ (fc = Fe(η-C5H4)2) 7 2 −7 9 (R = R‘ = H), 8 2 −8 7 (R = H and R‘ = SiMe3), and 9 2 −9 7 (R = R‘ = SiMe3) have been prepared and studied (the subscript n in the oligomer refers to the number of ferrocene units present). These species were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
303
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 350 publications
(331 citation statements)
references
References 64 publications
26
303
0
2
Order By: Relevance
“…Manners and co-workers have developed ferrocene polymers with various bridging moieties in the main chains [29], and they found that silicon bridged ferrocene polymers have two redox peaks due to the strong metal-metal interaction [30]. It has been reported that the initial oxidation occurs at alternating iron sites and subsequent oxidation occurs at a higher potential due to the charge repulsion between the iron sites [31]. In addition, it was reported that doped ferrocene polymers possess semiconductor characteristics [32].…”
Section: Ferrocene Polymersmentioning
confidence: 99%
“…Manners and co-workers have developed ferrocene polymers with various bridging moieties in the main chains [29], and they found that silicon bridged ferrocene polymers have two redox peaks due to the strong metal-metal interaction [30]. It has been reported that the initial oxidation occurs at alternating iron sites and subsequent oxidation occurs at a higher potential due to the charge repulsion between the iron sites [31]. In addition, it was reported that doped ferrocene polymers possess semiconductor characteristics [32].…”
Section: Ferrocene Polymersmentioning
confidence: 99%
“…A schematic of the cell is shown in Fig. 2a, and consists of the 17 . The cyclic voltammogram of this material (measured in a three-electrode configuration; Fig.…”
mentioning
confidence: 99%
“…21,92,[111][112][113] This is indicative of a stepwise process where initial oxidation at alternating iron centres occurs, because as one iron centre is oxidised ( 1 E1/2), the neighbouring sites become more difficult to oxidise (Scheme 9). Thus a higher potential is required ( 2 E1/2), resulting in the two oxidation waves with redox coupling, ∆E1/2 = 2 E1/2 -1 E1/2 (≈ 250 mV for PFSs).…”
Section: Redox and Charge Transport Propertiesmentioning
confidence: 99%
“…Thus a higher potential is required ( 2 E1/2), resulting in the two oxidation waves with redox coupling, ∆E1/2 = 2 E1/2 -1 E1/2 (≈ 250 mV for PFSs). 92 When identical experimental conditions are used for the electrochemical experiments (including the use of the same solvent and supporting electrolyte) the separation of the two waves, ∆E1/2, provides an approximate measure of the electronic interaction between iron centres along the polymer backbone. 114 Studies of isolated linear and cyclic oligomers has shown that the equal intensity, two redox-wave pattern characteristic of PFS materials corresponds to the limiting case of an infinite chain.…”
Section: Redox and Charge Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation